Flocculation behavior and mechanism of bioflocculant produced by Aspergillus flavus. (1st March 2015) - Aljuboori, Ahmad H. Rajab; Idris, Azni; Al-joubory, Hamid Hussain Rijab; Uemura, Yoshimitsu; Ibn Abubakar, B.S.U.
Abstract: In this study, the flocculation behavior and mechanism of a cation-independent bioflocculant IH-7 produced by Aspergillus flavus were investigated. Results showed 91.6% was the lowest flocculating rate recorded by IH-7 (0.5 mg L −1 ) at pH range 4–8. Moreover, IH-7 showed better flocculation performance than polyaluminum chloride ( PAC ) at a wide range of flocculant concentration (0.06–25 mg L −1 ), temperature (5–45 °C) and salinity (10–60% w/w). The current study found that cation addition did not significantly enhance the flocculating rate and IH-7 is a positively charged bioflocculant. These findings suggest that charge neutralization is the main flocculation mechanism of IH-7 bioflocculant. IH-7 was significantly used to flocculate different types of suspended solids such as activated carbons, kaolin clays, soil solids and yeast cells. Highlights: Cation-independent bioflocculant named as IH-7 is produced by Aspergillus flavus . IH-7 shows superior flocculating properties at different conditions. The rate of IH-7 flocculation is significantly higher than polyaluminium chloride. It could flocculate a variety of suspended solids. Charge neutralization is the proposed flocculation mechanism of IH-7.